The Marketing Strategy of Brens Bakery Business in Manna City of South Bengkulu Regency - Endah Permata Sari; Meiffa Herfianti; Zahrah Indah Ferina (Penerbit Jurnal Indonesia, 2021)
The purpose of this study is to determine the marketing strategy of Brens Bakery business in Manna city, South Bengkulu Regency. According to Assuari (2010: 168), marketing strategy is basically a comprehensive, integrated and unified plan in the marketing field, which provides guidance on activities to be carried out to achieve the marketing objectives of a company. The sample in this study were 51 people consisting of 6 employees of the Brens Bakery Business in Manna City, South Bengkulu Regency for internal factors and 45 people for external factors, namely customers at Brens Bakery Business in Manna City, South Bengkulu Regency. The analysis method used was SWOT analysis, which consists of the Internal Strategy Factor Matrix (IFAS) and the External Strategy Factor Matrix (EFAS). The results showed that the marketing strategy of Brens Bakery Business in Manna City, South Bengkulu Regency supported the aggressive strategy, or SO strategy in SWOT matrix. The result of strengths are 18.52 while the weaknesses are 9.24, so the internal quadrant of the factors is 18.52 - 9.24 = 9.28. It means that the ability of Brens Bakery Business in Manna City, South Bengkulu Regency in utilizing strengths and minimizing weaknesses contained in the internal company. The opportunity of this strategy are 17.40 and threat is 10.48. So the external quadrant factor, namely 17.40 - 10.48 = 6.92 means the high ability of Brens Bakery Business in Manna City, South Bengkulu Regency in taking advantage of opportunities and overcoming threats faced by companies in marketing bread